Toxicity and antioxidant assessment of ethanol leaf extract of Hibiscus surattensis in Wistar rats: hepatotoxicity evaluation - Israel Kevin Umana; Tobechukwu Anthony Tochukwu; Enoluomen Ehigiator; Chinedu Joseph Ikem; Godswill James Udom; Akinyele Olubiyi Akinsola (African Journal of Pharmaceutical Research and Development (AJOPRED))
Hibiscus surattensis is a medicinal plant with a vast beneficial use in the management and cure of a variety of diseases, ranging from urethritis to inflammation and vertigo among others. Notwithstanding the population's increasing use of it, particularly in rural regions, there is still lack of adequate investigation into its toxicity profile. The aim of this study was to investigate the ethanolic extract of Hibiscus surattensis leaf's potential for hepatotoxicity in Wistar rats. The acute toxicity test was carried out in two phases (phases 1 and 2). Phase 1, used nine mice which were randomized into three groups (n=3), receiving graded doses of the extract as follows: 10, 100, and 1000 mg/kg, ip respectively. Phase 2 used three mice which were randomized into three groups of one mouse each and administered the extract in graded doses of 2000, 3500, and 5000 mg/kg, ip, respectively. They were monitored for behavioral abnormalities, toxicity signs, and mortality for 24 hours following treatment. A subacute toxicity experiment was then carried out, in which Wistar rats were given oral doses of H. surattensis extract (141, 282, and 424 mg/kg) every day for eight (8) days. Behavioural changes, haematological and liver function parameters, in-vivo oxidative stress markers and histological changes were then evaluated. The LD50 of H. surattensis leaf extract was estimated to be 1414 mg/kg. Results revealed significant rise (p<0.01-0.001) in the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), conjugated bilirubin (C.B) and total bilirubin (T.B), as well as in white blood cell (WBC) and platelet at high doses of the extract-treated rats compared to control. A significant reduction was recorded in catalase among other antioxidant parameters while the histopathological evaluations showed mild alterations. While caution is urged during long-term administration, administration of H. surattensis ethanolic extract may be safe at the dosages studied in this investigation.